ACTR-57. A PHASE 1/2 STUDY TO EVALUATE THE SAFETY AND EFFICACY OF BLOOD-BRAIN BARRIER (BBB) OPENING WITH A NINE-EMITTER IMPLANTABLE ULTRASOUND DEVICE IN RECURRENT GLIOBLASTOMA PATIENTS PRIOR TO CARBOPLATIN. (11th November 2019) - Idbaih, Ahmed; Ducray, François; DeGroot, John; Stupp, Roger; Guyotat, Jacques; Lesniak, Maciej S; Sonabend, Adam; Weinberg, Jeffrey; Desseaux, Carole; Canney, Michael; Schmitt, Charlotte; Carpentier, Alexandre
Abstract: The blood-brain barrier (BBB) limits penetration of systemically administered therapies to brain tumors and peritumoral tissue and may be responsible for the failure of numerous drugs in recent clinical trials for glioblastoma (GBM). Low intensity pulsed ultrasound (LIPU), with concomitant intravenous microbubble injection (DEFINITY®), can temporarily disrupt the BBB for 6–24 hours and allow for enhanced delivery of drugs to the brain. In previous clinical studies, a 1-cm ultrasound (US) device, SonoCloud-1, was implanted in a burr hole of recurrent GBM patients ( n =27) and used to disrupt the BBB prior to carboplatin infusion at AUC5. This ongoing pilot phase 1/2 study (NCT03744026) aims to evaluate the safety and efficacy of transient opening of the BBB by LIPU in rGBM with the SonoCloud-9, a larger nine-emitter implantable device, designed to cover the tumor and surrounding infiltrative regions. The ultrasound device is implanted in a 6 cm x 6 cm bone flap window after tumor debulking surgery. Patients receive a 270-second sonication every month with concomitant microbubble injection to disrupt the BBB followed by carboplatin infusion at AUC4-6. Magnetic resonance imaging (MRI) is performed to verify safety and extent of BBB disruption. This study began enrollment in early 2019 and is an international, open-label, single arm, multi-site, dose-escalation and expansion trial to evaluate the safety of escalating sonication volume ("dose") with concurrent carboplatin. The number of activated emitters in the implant (3, 6, 9) is increased using a 3 + 3 dose escalation design. Safety data of the escalation phase of the study will be presented.